Decision Making Theory to Help Chief Executive Officer (CEO) for Company Management - Cicilia Niluh Deabona Sanjaya; Herlina, Dinda; Firdinisa, Naswa Rihadatul; Hidayat N, Rusdi; Kusumasari, Indah Respati (Indonesian Journal Publisher, 2024)
The purpose of this article is to identify theories of managerial decision making that are useful for CEOs and to identify factors that influence CEO decisions. The method used in this research is a literature review which reviews the results of several previous studies using the latest references from Google Schoolers and Mendeley citation searches. Based on the research conducted, it was concluded that decision theory helps CEOs in their management. Decision theory not only helps CEOs choose the right actions for the company, but also helps them predict and manage the possible consequences of those decisions.